Analisis Pesan Dakwah Ustadz Abi Azkakia dalam Game Mobile Legend - Raid, Dzaky Muhtadi; Syarifudin, Achmad; Muslimin (Pubmedia Social Sciences and Humanities, 2024)
This thesis is entitled "Analysis of Ustadz Abi Azkakia's Da'wah Message in the Mobile Legend Game". The aim of the first research is to analyze Ustadz Abi Azkakia's Da'wah message in the Mobile Legend Game and to find out the factors that influence the delivery of Ustadz Abi Azkakia's da'wah message in the Mobile Legend Game. The problem in research is that the Nurul Legend Council has recently attracted a lot of interest among young people because of the creativity of Ustadz Abi Azkakia who presents a da'wah nuance on the mobile legend platform. The preacher who presents the new Viber in the Mobile Legends game has his own meaning and method in conveying his preaching. The research uses qualitative methods. Data collection techniques through observation, interviews and documentation. The results of the research show that firstly, the Nurul Legend Council has recently attracted a lot of interest among young people because of the creativity of Ustadz Abi Azkakia who presents a preaching feel on the mobile legend platform. The preacher who presents the new Viber in the Mobile Legends game has his own meaning and method in conveying his preaching. Second, the factors that influence the delivery of preaching messages from Ustadz Abi Azkakia in the Mobile Legend Game are correcting dirty words from followers of the mobile legends game Tiktok account, replacing swearing with Dhikr and avoiding discussing the Dajjal as a joke. Bearing this in mind, the form of conveying a da'wah message does not have to be done monotonously and continuously.